Income taxes in Libya An Historical and Analytical study - بيت المال, محمد (Dirasat in Economics and Business, 1981)
The purpose of this study is to review the development of the income tax structure in Libya. To make the review clear and complete, the study is divided into four sections. The first section reviews the income tax structure before World War Il. The second section reviews the income tax structure after World War Il to 1968. The third section reviews the income tax structure from 1968 — 1973 (the current tax law was issued in 1973). The fourth section criticizes the income tax law No. 64 of 1973. The study shows how far the income tax structure was developed, and how much it will have to be developed. Of course the legislator will not succeed in having an appropriate tax law, which meets the social and economical conditions of the country, and in achieving this equitable balance, unless he submits the tax structure to a most rigorous, objective, comprehensive, and scientific study. Such a study cries out to be done in Libya.